Students' Perceptions and Challenges of Using Google Translate in EFL Writing Classes: A Mixed Methods Study in Vocational Education - I Kadek Dian Satriawan; Anak Agung Putri Maharani; Ida Bagus Nyoman Mantra (Al-Qalam Institute, 2026)
Google Translate has become a routine writing aid for students learning English as a foreign language, and vocational high school learners in Indonesia rely on it heavily. Research on this group remains limited, and most existing studies emphasize the technical accuracy of machine translation rather than how students themselves perceive the tool. This study examines how vocational high school students perceive the use of Google Translate in writing classes and identifies the challenges they encounter while using it. The study adopted an explanatory sequential mixed methods design grounded in the Technology Acceptance Model. Quantitative data were collected through a questionnaire completed by 175 eleventh-grade students at a tourism vocational school in Bali, and qualitative data were drawn from structured interviews with twelve of them. The findings reveal a clear gradient of acceptance. Positive endorsement was strongest for perceived ease of use and declined steadily through perceived usefulness and attitude toward using to behavioral intention, where reservations were strongest. Students valued the tool for its speed, simplicity, and vocabulary support, and they deliberately limited their reliance on it because they feared dependence and distrusted its accuracy in longer sentences. The pedagogical implication is that teachers should position Google Translate as a resource for critical review and revision rather than a substitute for learning, so that its convenience supports writing development without eroding language competence. This study contributes a perception-based account that extends acceptance research in vocational EFL contexts.